2017
DOI: 10.1515/jccm-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry During the First 24 Hours as a Screening Tool For Congenital Heart Defects

Abstract: IntroductionAlthough screening for congenital heart defects (CHD) relies mainly on antenatal ultrasonography and clinical examination after birth, life-threatening cardiac malformations are often not diagnosed before the patient is discharged.AimTo assess the use of routine pulse oximetry in the delivery room and at 24 hours postpartum, and to study its feasibility as a screening test for CHD.Material and MethodsIn this prospective study, all infants born in “Cuza Voda” Maternity Hospital, Iasi, Romania, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
6
0
5
Order By: Relevance
“…The predominant language in which the studies were published was English and the type of study was observational, retrospective and prospective. Nine studies (20)(21)(22)25,29,30,33,39,43,44) followed a protocol to perform the test in the first 24 hours, and the others from 24 hours after birth to 48 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant language in which the studies were published was English and the type of study was observational, retrospective and prospective. Nine studies (20)(21)(22)25,29,30,33,39,43,44) followed a protocol to perform the test in the first 24 hours, and the others from 24 hours after birth to 48 hours.…”
Section: Resultsmentioning
confidence: 99%
“…As for the sample, it varied in the size of the studies. Most of them analyzed one hospital, but there were studies analyzing more than 14 hospitals (23,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) . Chart 1 demonstrates the characteristics of the studies, considering participants, test period, cutoff points, and care behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, sensitivity of pulse oximetry screening was found to be 93% for detection of CCHD. Several studies have shown that when pulse oximetry is done in the first 24 hours of life, there can be more false positives 4,11 . In our study, pulse oximetry was done between 24-72 hours age.…”
Section: Discussionmentioning
confidence: 99%
“…Though antenatal ultrasonography usually detects major CHD, they can be missed, especially in developing countries, because of the absence of routine antenatal visits 4 . Pulse oximetry is a noninvasive tool used to detect CCHD 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Erken yapılan bir çalışmada 4. saatte taramada özgüllük %94, duyarlılık %75, yalancı pozitiflik %5,6 bulunmuştur [15]. Başka bir çalışmada 1. saatte özgüllük %95,5, duyarlılık %87,5 iken 24. saatinde özgüllük %97,5; duyarlılık %92,5 saptanmış ve doğum sonrası ilk saat boyunca pulse oksimetre takibinin zamanında müdahaleyi kolaylaştırmak için KKH'nin erken bir göstergesi olduğu belirtilmiştir [16]. Geç tarama, 24 saatten sonra yapılır, iş yükü daha az, yalancı pozitiflik daha az, ancak bazı olgularda tanıda gecikme riski olabilir [8].…”
Section: Bulgular Ve Tartışmaunclassified